Determination of Physico-Chemical Properties of Z-spinachristi (Nabag ) Seed Crude Oil - Khair Elseed, Awadia Saeed; S. Shakak, Mahdi Abbas (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
This study was conducted to determine the physical and chemical properties of Nabag seed crude oil .The proximate composition of seed of Zizyphus spina-christi fruit were moisture content (4.59%), oil content (28.96%), protein content (16.03%), crude fiber (9.57%) ,ash content (4.47%), and total carbohydrate (36.38%). The physical properties of Z. spina –Christi seed oil were refractive index (1.4670), the density (0.9339), the viscosity(33.26 cp), and the colour (1.16 R,20(Y).While the chemical properties were the peroxide value (0.5), the acid value (1.19) , the iodine value (117.38) ,and saponification value (181.39). The main unsaturated fatty acids were oleic acid (57%), and linoleic (22%), while the major saturated fatty acids plamitic acid (7.2%) ,stearic acid (4.7%) and arachidic acid (6.7%).